Enhanced adsorption capacity of activated carbon over thermal oxidation treatment for methylene blue removal: kinetics, equilibrium, thermodynamic, and reusability studies. Issue 1 (21st December 2022) - Kurnia, Irwan; Karnjanakom, Surachai; Irkham, Irkham; Haryono, Haryono; Situmorang, Yohanes Andre; Indarto, Antonius; Noviyanti, Atiek Rostika; Hartati, Yeni Wahyuni; Guan, Guoqing
Abstract : Thermal air oxidation enhances the adsorption capacity of steam-activated carbon coconut shell (SACCS) on MB removal and recovers the adsorption ability of the spent SACCS treated at 350 °C. Abstract : Activated carbon (AC) is an effective and inexpensive adsorbent material for dye removal, but it cannot always be used repeatedly. Furthermore, the adsorbed dyes with toxicity usually remain on its surface. In this study, a thermal air oxidation process was used to modify the surface of AC and decompose adsorbed methylene blue (MB). The behavior of this process on spent AC was investigated using TGA-DTA, while the degradation of MB before and after the regeneration process was analyzed using a carbon, hydrogen, nitrogen, sulfur (CHNS) analyzer. It was discovered that thermal air oxidation could promote the formation of oxygenated functional groups on AC produced from steam-activated carbon coconut shell (SACCS), which when treated at 350 °C (denoted as SACCS-350), demonstrated an adsorption capacity 2.8 times higher than the non-air-oxidized AC (SACCS). The key parameters for the MB adsorption of SACCS and SACCS-350, such as kinetics, equilibrium, and thermodynamics, were compared. Moreover, the SACCS-350 could be reused at least 3 times for the adsorption of MB. Based on these results, thermal air oxidation treatment could successfully improve the adsorption performance of AC and regenerate spent AC through a reasonable and environmentally friendly process compared to other regeneration methods.